Iron-based subsurface arsenic removal (SAR): Results of a long-term pilot-scale test in Vietnam. (15th August 2020) - Cañas Kurz, Edgardo E.; Luong, Vu T.; Hellriegel, Ulrich; Leidinger, Felix; Luu, Tran L.; Bundschuh, Jochen; Hoinkis, Jan
Abstract: The principle of subsurface arsenic removal (SAR) from groundwater is based on oxidation and adsorption reactions by infiltrating oxygen into the anoxic aquifer and the immobilization of arsenic (As) onto freshly formed iron (Fe)-(hydr)oxides. In this study, a pilot-scale plant for SAR has been subject to long term testing in the Mekong Delta, Vietnam. Initial concentrations of Fe (8.4 ± 1.3 mg L −1 ) and As (81 ± 8 μg L −1 ) in the exploited groundwater were successfully lowered to below the WHO guideline value limits for drinking water of 0.3 mg L −1 and 10 μg L −1, respectively. Adsorption and co-precipitation of As with Fe-(hydr)oxides could be identified as the principal mechanism responsible for the As removal from groundwater, demonstrating the feasibility of SAR as a low-cost and zero-waste solution over a period of two years. However, naturally occurring geochemical reducing conditions and high ammonium levels in the groundwater delayed the removal of manganese (Mn). An additional post-treatment filtration for Mn-removal was temporarily used to comply with the Vietnamese drinking water standard until a Mn-mitigation was achieved by the SAR process. In contrast to most As-remediation technologies, SAR appears to be a long-term, sustainable treatment option with the salient advantage of negligible production of toxic waste, which with ex-situ processes require additionally management costs. Graphical abstract: Image 1 Highlights: A pilot plant for subsurface arsenic removal (SAR) was operated for over 2 years. Arsenic was successfully lowered to below WHO drinking water guideline. No remobilization of As was observed for 28 months operation. SAR is a low-cost sustainable method with no toxic waste produced.